Application of local microorganisms from tuna fish and shrimp waste as bio activator for household organic waste composting by Takakura method. Issue 1 (November 2021) - Dewilda, Y; Aziz, R; Rahmayuni, F
Abstract: Organic waste has the potency to use as bio activator material. This research compares household organic waste compost results with the addition of bio activator from local microorganism activator (LMO) from tuna fish and shrimp waste with Effective Microorganisms (EM4). The composting method used is aerobic composting with the Takakura composting technique. This composting is carried out in 5 variations, variation one without-bio activator added, 2 with LMO of tuna fish waste added, variation 3 with LMO shrimp waste added, variation 4 with LMO of tuna fish, and shrimp waste added, variation 5 with EM4 added. Analysis of all compost quality has met SNI 19-7030-2004 standards. A total of 2 kg of raw material produced solid compost becomes 0.7-1 kg of compost. The use of bio activators can speed up the composting process to 8-12 days. The variation of adding LMO tuna fish waste was chosen as a suitable alternative compared to other variations. The composting process with LMO of tuna fish waste results from the fastest composting time of 9 days with a C/N ratio of 18.45%, P2 O5 0.56 %, and 0.76% K2 O, with 0.85 kg of compost. Scoring results in variation 2 is the best variation in compost maturity quality.